Prevalence of Exposure to Complex Trauma and Community Violence and Their Associations With Internalizing and Externalizing Symptoms - Yearwood, Karen (Journal of interpersonal violence, 2021)
Studies about trauma often tend to focus on abuse and neglect. However important, these studies may neglect the importance of the broader community context that is often associated with trauma, and complex trauma (CT) in particular. This study aimed to investigate the effects of CT (defined in terms of experiencing abuse and/or neglect occurring in the context of relationships with caregivers), and of broader environmental adversity (i.e., exposure to community violence), in a sample of adolescents (N = 218) from a severely disadvantaged district of Lima, Peru. The study had two aims: (a) to assess the prevalence of CT and its associations with internalizing and externalizing symptoms in these adolescents and (b) to investigate the associations between community violence and both internalizing and externalizing symptoms over and above the effects of CT. In total, 39.4% of the adolescents reported at least one type of moderate to severe trauma. There was a clear association between CT and both internalizing and externalizing symptoms. Ordinal logistic regressions showed that children who were exposed to one or more traumatic experiences were more likely to score within a higher range of internalizing and externalizing symptoms than children with no history of trauma. Finally, exposure to community violence was an important predictor of symptomatology beyond the effects of CT.